2022
DOI: 10.1038/s41467-022-29264-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a protein responsible for the synthesis of archaeal membrane-spanning GDGT lipids

Abstract: Glycerol dibiphytanyl glycerol tetraethers (GDGTs) are archaeal monolayer membrane lipids that can provide a competitive advantage in extreme environments. Here, we identify a radical SAM protein, tetraether synthase (Tes), that participates in the synthesis of GDGTs. Attempts to generate a tes-deleted mutant in Sulfolobus acidocaldarius were unsuccessful, suggesting that the gene is essential in this organism. Heterologous expression of tes homologues leads to production of GDGT and structurally related lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 72 publications
3
76
1
1
Order By: Relevance
“…The anticipated biochemical mechanism for MSL synthesis is based on the dimerization of the FA building blocks through the formation of a carbon-carbon bond between either the ω -1 carbon of C 16 FAs or the ω carbon of iso -C 15:0 FAs to form DA or iso -DA, respectively 8,1 . A radical reaction mechanism for the formation of MSLs in bacteria has been previously proposed 27 , and recently confirmed for the synthesis of the isoprenoid MSLs in Archaea 9 . This reaction would involve a radical intermediate formed by a hydrogen extraction at the tail of one of the fatty acids, followed by a condensation with the other tail, involving the loss of another hydrogen, resulting in the formation of a C-C bond in the absence of an activated intermediate.…”
Section: In Search For Potential Proteins For the Biosynthesis Of Mem...mentioning
confidence: 76%
See 2 more Smart Citations
“…The anticipated biochemical mechanism for MSL synthesis is based on the dimerization of the FA building blocks through the formation of a carbon-carbon bond between either the ω -1 carbon of C 16 FAs or the ω carbon of iso -C 15:0 FAs to form DA or iso -DA, respectively 8,1 . A radical reaction mechanism for the formation of MSLs in bacteria has been previously proposed 27 , and recently confirmed for the synthesis of the isoprenoid MSLs in Archaea 9 . This reaction would involve a radical intermediate formed by a hydrogen extraction at the tail of one of the fatty acids, followed by a condensation with the other tail, involving the loss of another hydrogen, resulting in the formation of a C-C bond in the absence of an activated intermediate.…”
Section: In Search For Potential Proteins For the Biosynthesis Of Mem...mentioning
confidence: 76%
“…In the same way, iso -DAs are believed to be produced by the condensation of two iso -C 15:0 FAs at the ω positions 1 , but the enzymes responsible for the formation of these types of bacterial MSLs (i.e., MSL synthases) remain elusive. A recent study has identified a radical SAM enzyme (tetraether synthase, Tes) responsible for the archaeal tail-to-tail coupling of two ether-bound phytanyl chains, enabling the synthesis of glycerol dialkyl glycerol tetraethers (GDGTs) 9 . Since Tes homologs were detected in bacterial genomes, they have been hypothesized to be involved in the synthesis of bacterial MSLs 9 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, tetraether synthase (Tes), a key protein responsible for the formation of archaeal isoprenoid GDGTs (isoGDGTs) via the combination of two archaeol molecules, has been identified (21). Bacterial brGDGTs bear a structural resemblance to archaeal isoGDGTs, i.e., both of them consisting of two alkyl chains linked to two glycerol backbones via four ether bonds (15).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial brGDGTs bear a structural resemblance to archaeal isoGDGTs, i.e., both of them consisting of two alkyl chains linked to two glycerol backbones via four ether bonds (15). The Tes protein could, therefore, also be involved in the biosynthesis of bacterial brGDGTs, since Tes homologs have been found in bacterial genomes of diverse phyla including Acidobacteria (21).…”
Section: Introductionmentioning
confidence: 99%